2012
DOI: 10.1159/000334620
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Change in the Localization of Recurrent or Persistent Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: Purpose: To investigate the change in localization of recurrent or persistent macular edema (ME) secondary to branch retinal vein occlusion (BRVO) after a therapeutic intervention. Methods: Twenty-six eyes of 23 patients with recurrent or persistent ME secondary to BRVO were included in this retrospective case series. We analyzed the distance between the fovea and the top of the ME (fovea–ME top distance) and the ME area using optical coherence tomography before treatment and when ME recurred or persisted. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Arema et al [ 18 ] used OCT to compare the location of ME and vascular leakage in patients with BRVO and showed that RME tends to shift from extrafoveal fields toward the fovea with time. Early detection and retreatment of RME may prevent damage to central vision by arresting ME before it encroaches on the fovea.…”
Section: Discussionmentioning
confidence: 99%
“…Arema et al [ 18 ] used OCT to compare the location of ME and vascular leakage in patients with BRVO and showed that RME tends to shift from extrafoveal fields toward the fovea with time. Early detection and retreatment of RME may prevent damage to central vision by arresting ME before it encroaches on the fovea.…”
Section: Discussionmentioning
confidence: 99%